M73 groundwater management - Bloetscher, Frederic (American Water Works Association, 2021)
"Manual M73 Groundwater Management is the culmination of efforts by members of the Groundwater Resource Committee to identify and demonstrate the value of using computer modeling tools to help utilities better manage their groundwater resources in light of greater competition for water and dwindling supplies in many parts of the world. I"-- Provided by publisher.
Keywords: Wells.; Groundwater.; Water-supply -- Management.; elektronické knihy; electronic books